Water resource research and education in mountain communities - Roa García, María Cecilia; Roa García, C.E.; Brown, S.; Cordero, E. (International Mountain Society (IMS) and United Nations University, 2008)
High elevation páramo (wetland) ecosystems in the Andes are important water sources for local communities and downstream agricultural and urban users. These headwater catchments, however, are often impacted by human activities (eg agricultural production) that affect both stream water quality and flow. Knowledge about water availability, quality, and use is essential for effective management but is often lacking, particularly in smaller mountain communities. Studies of natural resources in mountains, conducted jointly with local actors and with the participation of youth, are a way for rural communities to learn about their resources, appropriate this knowledge, and improve their quality of life. Research projects that involve youth in remote rural zones, where education is not of the same quality as in urban centers, represent an important opportunity for youth to acquire skills and relevant knowledge for their personal development and for participation in development processes. The present article presents a process and the results of a project that studied water resources in Bolivia and Colombia with local youth and water users. The research themes in the 2 countries were different, responding to the concerns of their respective communities, but the results had a similar major impact on the lives of young researchers, on the communities' perception of the state of their natural resources in particular water and on the role of knowledge in generating creative options for improving resource management and the quality of life in mountain communities.